Children's viewing of cartoons and its relationship to their social behavior: within the framework of parental mediation theory (The International Journal of Educational Sciences and Arts, 2025)
The current study aims to determine the concept of the impact of children watching cartoons, and to shed light on their relationship to their social behavior within the framework of the parental mediation theory. To achieve the study's goal, the researcher will rely on the descriptive survey approach in the current study to provide a deep insight into this important segment of society. The researcher will also use the questionnaire tool in the current study to collect data by applying the study sample to parents residing in the Eastern Province in the city of Al-Ahsa who have children in the early childhood stage. The current study derives its theoretical framework from the parental mediation theory. The current study will test the hypothesis of the theory on parents when their children are exposed to cartoons. The study data was analyzed using the SPSS program. The current study came out with a set of results, the most prominent of which are: The results showed that the most prominent positive effects that a child acquires from watching cartoons are (acquiring language skills) at a rate of (66.67%), while the results showed that the most prominent negative effects that a child acquires from watching cartoons are (laziness and inactivity) at a rate of (40.20%). The study proved that the majority of children (sample members) are not affected by the character of cartoons. The degree represented by (sometimes) was (54.9%). The results showed that parents are aware of the importance of setting a specific time for children to watch cartoons, and that they seek to achieve a balance between entertainment and duties, as parents’ keenness to set a time period for their children to watch cartoons (always) reached the highest percentage of 43.1%.
Keywords: Cartoon Films; Social Behavior; Early Childhood